Genetic Diversity of Prolactin Gene in Japanese Quail (Coturnix coturnix japonica) as Affected by Location in Nigeria (2016)
Restriction fragment length Polymorphism (RFLP) marker was used to investigate the effect of location on polymorphism, relationship and population structure with respect to prolactin gene (PRL gene) in Japanese quails in Nigeria. Blood samples were collected from thirty quails each from 5 different regions (North, South, West, East and North Central), for PRL loci analysis. DNA was extracted from the samples. Polymerase chain reaction (PCR) and electrophoresis was used to characterize a 24 base pair (bp) insertion/deletion (Indel) in a 358 bp PCR product. The populations were characterized for their genetic variability using allele frequencies, polymorphic information content, observed heterozygosity (Ho), genetic distance (D), F-statistics (FIT, FIS, FST), analysis of molecular variance, test for Hardy-Weinberg Equilibrium (H-WE) and cluster analysis. Two alleles A (0.35 to 0.63) and B (0.37 to 0.65) were observed at the PRL gene loci. The highest FIT was recorded between 0.10 (East) and 0.19 (North) indicating inbreeding within the population. The FIS among populations were between 0.09 (North central) and 0.14 (North) while FST ranged from 0.001 (North central) to 0.06 (North), indicating moderate genetic differentiation among populations. Chi Square result indicated that the population were not in H-WE. The phylogenetic relationships showed that the population from the 5 regions had common descent. Clusters from the combined population showed that PRL gene is based on individual genotype and not location. AMOVA analysis showed that 3% of the total genetic variation was explained by population difference, 19% by variation among individuals and 77% within individuals. The results showed that study of prolactin gene diversity is useful for decision making for selective breeding and conservation strategies for Japanese quails irrespective of the location.